Mono‐ and Hetero‐Dinuclear Complexes of Janus‐Head NHC Ligands Possessing Backbone Phosphinoyl Groups: the Case of Soft and Hard Metal Centers1. Issue 29 (25th August 2014) - Majhi, Paresh Kumar; Serin, Spencer C.; Schnakenburg, Gregor; Gates, Derek P.; Streubel, Rainer
Abstract: The synthesis and structures of Rh I and Ir I complexes bearing 4‐phosphinoyl‐ and 4, 5‐bis(phosphinoyl)imidazol‐2‐ylidene ligands (NHC P ) is reported. Deprotonation of the corresponding imidazolium hydrogen sulfate salts by KO t Bu in the presence of [M(cod)Cl]2 afforded complexes of the formula [M(cod)Cl(NHC P )] [5a/5b : NHC P = 4‐Ph2 P(O)‐I i PrMe, 5a : M = Rh, 5b : M = Ir and7a/7b : NHC P = 4, 5‐Ph2 P(O)2 ‐I n BuMe]. The Rh I complexes5a and7a were then converted into [Rh(CO)2 Cl(NHC P )]8a and9a via reaction with carbon monoxide; the average CO stretching frequencies [8a :ν (CO)av = 2036 cm –1 and9a :ν (CO)av = 2038.4 cm –1 ] led to the conclusion that mono‐ and bis‐functionalized NHC P s act as relatively weaker donors than backbone unsubstituted NHC. A first examination of Janus‐head ligand properties of complex7a revealed that reaction with TiCl4 afforded hetero‐dinuclear10a, a′ as a mixture of isomeric monodentate phosphinoyl titanium(IV) adducts. All products were characterized by elemental analyses, spectroscopic and spectrometric methods and, in addition, complexes7a and7b by single‐crystal X‐ray structure analysis. Abstract : A family of hybrid ligands composed of hard phosphine oxides and soft N‐heterocyclic carbene donor sites have been employed to synthesize [M(cod)Cl(NHC P )] complexesI, which were further converted into the corresponding dicarbonyl complexes in order to study their donor properties. The advantage of backbone phosphinoyl groups was exploited to generate hetero‐dinuclear Ti IV, Rh I complexes10a, a′ .